Ekspresi dan Aktivasi Sub Unit p65 NF-κB pada Sel Mononuklear Penderita Sindrom Nefrotik Resisten Steroid Anak - Corebima, Brigitta Ida RV; Subandiyah, Krisni; Fitri, Loeki Enggar (Fakultas Kedokteran Universitas Brawijaya, 2009)
Resitance to steroid therapy is a poor prognosis sign for nephrotic syndrome, but this mechanism is still unclear. NF-κB has been reported to affect the glucocorticoid at the T cell through the transrepression in the glucocorticoid receptor . Until know, this study was still limited. The aim of this study was to show the difference expression and activation of NF-κB p65 subunit between childhood SRNS and SSNS patient. Cross sectional study was conducted during January 2009 to December 2009 in the Saiful Anwar General Hospital and Biomedic Laboratory Brawijaya University. Expression and activation of NF-κB p65 subunit were determine by immunochemistry staining by counting the amount of lymphocyte that express and activate NF-κB p65 subunit among 200 lymphocytes under light microscope with 1000 magnification. Results was analyzed by independent t test with 95% CI (p<0,05) and Pearson correlation. The result of this study revealed no significant difference of expression of NF-κB p65 subunit between SRNS and SSNS (p=0,153), but there was an increase activation of NF-κB p65 subunit in the SRNS patients (p=0,000).